Serum and cerebrospinal fluid phosphorylated neurofilament heavy subunit as a marker of neuroaxonal damage in tick-borne encephalitis - Fortova, Andrea; Hönig, Vaclav; Palus, Martin; Salat, Jiri; Pychova, Martina; Krbkova, Lenka; Vyhlidalova, Tereza; Kriha, Michal F; Chrdle, Ales; Ruzek, Daniel (The Journal of general virology, 2022)
Extensive axonal and neuronal loss is the main cause of severe manifestations and poor outcomes in tick-borne encephalitis (TBE). Phosphorylated neurofilament heavy subunit (pNF-H) is an essential component of axons, and its detection in cerebrospinal fluid (CSF) or serum can indicate the degree of neuroaxonal damage. We examined the use of pNF-H as a biomarker of neuroaxonal injury in TBE. In 89 patients with acute TBE, we measured CSF levels of pNF-H and 3 other markers of brain injury (glial fibrillary acidic protein, S100B and ubiquitin C-terminal hydrolase L1) and compared the results to those for patients with meningitis of other aetiology and controls. Serum pNF-H levels were measured in 80 patients and compared with findings for 90 healthy blood donors. TBE patients had significantly (P<0.001) higher CSF pNF-H levels than controls as early as hospital admission. Serum pNF-H concentrations were significantly higher in samples from TBE patients collected at hospital discharge (P<0.0001) than in controls. TBE patients with the highest peak values of serum pNF-H, exceeding 10 000 pg ml-1, had a very severe disease course, with coma or tetraplegia. Patients requiring intensive care had significantly higher serum pNF-H levels than other TBE patients (P<0.01). Elevated serum pNF-H values were also observed in patients with incomplete recovery (P<0.05). Peak serum pNF-H levels correlated positively with the duration of hospitalization (P=0.005). Measurement of pNF-H levels in TBE patients might be useful for assessing disease severity and determining prognosis.
Keywords: prognóza; Prognosis; Intermediate Filaments; Humans; intermediární filamenta; lidé; biomarker; klíšťová encefalitida; progrese nemoci; biologické markery; neurofilament; flavivirus; tick-borne encephalitis; Biomarkers; Disease Progression; brain injury; Encephalitis, Tick-Borne